2018
DOI: 10.1007/s11427-018-9385-3
|View full text |Cite
|
Sign up to set email alerts
|

Chinese society of cardiology expert consensus statement on the diagnosis and treatment of adult fulminant myocarditis

Abstract: Fulminant myocarditis is primarily caused by infection with any number of a variety of viruses. It arises quickly, progresses rapidly, and may lead to severe heart failure or circulatory failure presenting as rapid-onset hypotension and cardiogenic shock, with mortality rates as high as 50%-70%. Most importantly, there are no treatment options, guidelines or an expert consensus statement. Here, we provide the first expert consensus, the Chinese Society of Cardiology Expert Consensus Statement on the Diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 96 publications
1
100
0
7
Order By: Relevance
“…In this case, the patient had the following features: sudden onset, obvious symptoms of viral infection, rapid emergence of severe hemodynamic disorders, severe myocardial injury, and diffuse decreased ventricular wall movement. The above features are all in accordance with the diagnostic criteria of fulminant myocarditis [5]. This patient's PASP gradually increased, suggesting that the pulmonary lesions were gradually aggravated.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this case, the patient had the following features: sudden onset, obvious symptoms of viral infection, rapid emergence of severe hemodynamic disorders, severe myocardial injury, and diffuse decreased ventricular wall movement. The above features are all in accordance with the diagnostic criteria of fulminant myocarditis [5]. This patient's PASP gradually increased, suggesting that the pulmonary lesions were gradually aggravated.…”
Section: Discussionsupporting
confidence: 83%
“…Bedside echocardiography showed an enlarged left ventricle (61 mm), diffuse myocardial dyskinesia along with a low left ventricular ejection fraction (LVEF) (32%), pulmonary hypertension (44 mmHg), and no decrease in right cardiac function (Figs. 4,5). No pericardial effusion was observed.…”
Section: Case Reportmentioning
confidence: 93%
“…In this study, we first reported that the infection of SARS-CoV-2 may cause fulminant myocarditis. Given that fulminant myocarditis is characterized by a rapid progress and a severe state of illness [3], our results should alert physicians to pay attention not only to the symptoms of respiratory dysfunction but also the symptoms of cardiac injury.…”
mentioning
confidence: 92%
“…immunoglobins, neuraminidase inhibitors, and active mechanical lifesupport treatments. The life-support treatments comprised the application of mechanical respirators and circulatory support systems, of which intra-aortic balloon pulsation (IABP) or Impella implantation or extracorporeal membrane oxygenation (ECMO) as well as cardiac pacemaker are part of the current therapeutic armamentarium [23]. The important and life-saving role of IABP, Impella, and ECMO has been underlined also by European and American centers [24][25][26].…”
Section: Viral Fulminant Myocarditismentioning
confidence: 99%